Embracing generative artificial intelligence: The perspectives of English instructors in Thai higher education institutions - Lucas Kohnke; Mark B. Ulla (Knowledge Management & E-Learning: An International Journal)
This study explored the perspectives of English instructors from Thai higher education institutions, with a focus on teachers’ familiarity with generative artificial intelligence (GenAI) and its potential impact on teachers’ professional roles and responsibilities. The results suggested that GenAI tools may allow English instructors to transition from traditional teachers to facilitators by using the tools to assist with both routine writing tasks and high-level academic work. Meanwhile, it was found that instructors worried about possible over-reliance on GenAI. The participants emphasised that human instructors were still needed, although their roles needed to evolve. Significant gaps were identified in the competencies related to professional development, curriculum design, teacher training programmes, ethics, and responsibility. The findings may support the professional growth of current and future English instructors and facilitate the incorporation of GenAI in teaching practice. The findings also underscore the necessity of comprehensive GenAI training for pre-service teachers, the development of robust guidelines to navigate ethical challenges, and the examination of the impact of GenAI tools on student engagement and learning outcomes.